2020
DOI: 10.3390/jcm9051464
|View full text |Cite
|
Sign up to set email alerts
|

Unrealistic Optimism in the Time of Coronavirus Pandemic: May It Help to Kill, If So—Whom: Disease or the Person?

Abstract: Objective: The results of numerous empirical studies have showed the occurrence of so-called unrealistic optimism. Thus, we aimed to investigate whether in the situation of an imminent coronavirus pandemic, people would still perceive themselves as being less exposed to the disease than others. Methods: Survey studies were conducted to examine the level of unrealistic optimism. Participants (n = 171, 67.3% of women) in a subjective way judged the risk of their coronavirus infection and the likelihood that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
95
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 22 publications
16
95
3
Order By: Relevance
“…In comparison, 5 con rm that unrealistic optimism was mainly observed in men in the three measures, but also women in two measures; therefore, the phenomenon of unrealistic optimism was observed especially among men. This study has several limits related to the time-sensibility of the pandemic (COVID-19).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In comparison, 5 con rm that unrealistic optimism was mainly observed in men in the three measures, but also women in two measures; therefore, the phenomenon of unrealistic optimism was observed especially among men. This study has several limits related to the time-sensibility of the pandemic (COVID-19).…”
Section: Discussionmentioning
confidence: 51%
“…The unrealistic optimism is de ned as the tendency for people to believe that they are "less likely to experience negative events and more likely to experience positive events than are other people". 5,6 The optimistic bias has been de ned as the result of the joint efforts of two mechanisms. The rst of these is related to cognitive factors such as lack of information and the poor critical insight into one's cognitive skills.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-lab study in ten different countries provided evidence for a positive relation between risk assessment and self-reported adoption of containment behaviors in regard to COVID-19 (Dryhurst et al, 2020). Other research supports ENDORSEMENT OF CLAIMS ABOUT COVID-19 6 the notion that the perceived risk of infection is linked to compliance and protective behavior in the Corona pandemic (De Neys et al, 2020;Harper et al, 2020;Dolinski et al, 2020).…”
Section: Trust In Science Risk Assessment and Compliance To Containmmentioning
confidence: 89%
“…The most recent research on COVID-19 refers to optimism bias and its contribution to the spread of the virus. The study revealed a general occurrence of unrealistic optimism: people perceived themselves as less exposed to the disease than others (Dolinski et al 2020). Participants of Kuper-Smith's study (2020) rated the chance of getting infected with COVID-19 lower for themselves than for other people similar to them regarding socio-demographic characteristics.…”
Section: Introductionmentioning
confidence: 95%